2020
DOI: 10.1111/exd.14217
|View full text |Cite
|
Sign up to set email alerts
|

Early transcriptional changes after UVB treatment in atopic dermatitis include inverse regulation of IL‐36γ and IL‐37

Abstract: Phototherapy with narrow‐band Ultraviolet B (nb‐UVB) is a major therapeutic option in atopic dermatitis (AD), yet knowledge of the early molecular responses to this treatment is lacking. The objective of this study was to map the early transcriptional changes in AD skin in response to nb‐UVB treatment. Adult patients (n = 16) with AD were included in the study and scored with validated scoring tools. AD skin was irradiated with local nb‐UVB on day 0, 2 and 4. Skin biopsies were taken before and after treatment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
18
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 58 publications
(63 reference statements)
2
18
1
Order By: Relevance
“…Narrow‐band UVB (nb‐UVB) is a major phototherapy option in both AD management and PSO management, but the early molecular responses to UVB are not clear. In a study by Lossius et al 79 . AD patients were irradiated with local nb‐UVB 3 times over a course of 7 days, and RNA‐seq analysis of the skin biopsies found that the expression of proinflammatory cytokine IL36 g was reduced, while the anti‐inflammatory cytokine IL37 was elevated after treatment, suggesting that modulation of the IL1 family cytokines may be the key early molecular responses during nb‐UVB therapy.…”
Section: Pharmacology and Drug Deliverymentioning
confidence: 99%
“…Narrow‐band UVB (nb‐UVB) is a major phototherapy option in both AD management and PSO management, but the early molecular responses to UVB are not clear. In a study by Lossius et al 79 . AD patients were irradiated with local nb‐UVB 3 times over a course of 7 days, and RNA‐seq analysis of the skin biopsies found that the expression of proinflammatory cytokine IL36 g was reduced, while the anti‐inflammatory cytokine IL37 was elevated after treatment, suggesting that modulation of the IL1 family cytokines may be the key early molecular responses during nb‐UVB therapy.…”
Section: Pharmacology and Drug Deliverymentioning
confidence: 99%
“…9 Furthermore, IL-37 transcripts were elevated after treatment of AD patients. 10 Thus, recombinant IL-37 was suggested as a potential therapeutic option for psoriasis and AD.…”
Section: Research Letter Dear Editorsmentioning
confidence: 99%
“…The phenotype (I stress phenotype here over genotype) of human skin and hair follicle pigmentation is an end‐product of a rather tortuous journey through at least five or six key, but distinct, elements of the melanocyte‐keratinocyte interaction unit, the EMU 39 . This spans the behaviour and fate of (a) tyrosinase, 40,41 (b) (pre)melanosome biogenesis and maturation, 42–44 (c) transport of melanosomes within the melanocyte, 45–47 (d) intercellular transfer of melanin granules to EMU keratinocyte partners, 48–53 (e) distribution of melanin within keratinocytes 52,54,55 and (f) the still enigmatic long‐term fate of melanin in the skin organ 27,52 . In that regard, for a discussion on how best to experimentally approach the discovery of new pigmentation modulators, I use the analogy of one of Aesop's favourite fable, The Tortoise and The Hare .…”
Section: Figurementioning
confidence: 99%
“…It does not appear, however, to facilitate, the important discrimination of melanocytes by melanin subtype, that is relative levels of brown/black eumelanin versus red/yellow pheomelanin. Much of the human skin phenotype is influenced by the ratio of both melanin subtypes in the epidermis, especially in the context of how the skin responds to light 28,39,46,47,53 …”
Section: Figurementioning
confidence: 99%